Reclaiming popular documentary - Milliken, Christie; Anderson, Steve F. (Indiana University Press, 2021)
"The documentary has achieved rising popularity over the past two decades, thanks to streaming services like Netflix and Hulu. Despite this fact, documentary studies still tends to favor works that appeal primarily to specialists and scholars. Reclaiming Popular Documentary reverses this longstanding tendency by showing that documentaries can be-and are-made for mainstream or commercial audiences. Editors Christie Milliken and Steve Anderson, who consider popular documentary to be a subfield of documentary studies, embrace an expanded definition of popular to acknowledge documentary's many evolving forms, including branded entertainment, fictional hybrids, and works with audience participation. Together, these essays address emerging documentary forms-including web-docs, virtual reality, immersive journalism, viral media, interactive docs, and video-on-demand-and offer the critical tools that viewers need in order to analyze contemporary documentaries and consider how they are persuaded by and represented in documentary media. By combining perspectives of scholars and makers, Reclaiming Popular Documentary brings new understandings and international perspectives to familiar texts using critical models that will engage media scholars and fans alike"--